PENGEMBANGAN E-MODUL BERBASIS PEMBELAJARAN BERDIFERENSIASI DALAM MENINGKATKAN KEMAMPUAN LITERASI NUMERASI PESERTA DIDIK KELAS XI SMA/MA - Fitriani, Nadya (Jurnal Edukasi dan Penelitian Matematika, 2024)
Abstract - The purpose of this paper was to determine the validity of e-modules based on differentiated learning in upgrading the numeracy literacy ability of class XI SMA/MA students. The type of research is development based on the Plomp model. The participants in the study included 32 students of class X and an educator. The following data were collected through questionnaires, documentation, and observation methods. Meanwhile, to analyse the data which is divided into stages, namely in the preliminary research phase, data reduction will be used, then data presentation as well as conclusion drawing, then analysis for product validity using a Likert scale. The results showed that the criteria for the validity of the e-module from the aspect of material substance obtained a validity value of 82.00, the feasibility aspect of the presentation of 89.45, the feasibility aspect of the material display of 88.80, in terms of material language of 87.20 and in terms of aspects of differentiated learning approaches and numeracy literacy with a validity value of 86.2. All aspects are in the valid criteria. Thus, for the average of all, the validity of the e-module from the five validators is 86.74, which is valid. Based on the explanation above, the e-module based on differentiated learning in improving the numeracy literacy skills of class XI SMA/MA students is valid.Keywords– Differentiated Learning, e-modules, numeracy literacy